2016
DOI: 10.5897/ijnm2015.0203
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent factors relating to the adoption of vasectomy among married men in peri-urban communities of Ibadan, Nigeria

Abstract: Vasectomy is a method of family planning which is quite acceptable in many developed countries of the world. However, in most African countries, there are still existing barriers to its adoption by married men. This study was therefore designed to explore the antecedent factors related to the adoption of vasectomy among married men in eight (8) peri-urban communities of Ibadan, Nigeria. Four hundred and thirty one men selected using multi-stage sampling technique were interviewed in a household survey using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…Sood et al also found that 52% of the men had fear of failure of vasectomy as it brings a bad name to wives in Punjab. 11 Fear of complications (3%) of the procedure after the surgery was another factor observed in our study which was coherent with studies done by Ayele et 8,12,13 These findings indicate the importance of addressing fears and providing adequate information to alleviate concerns and promote informed decision-making regarding the procedure.…”
Section: Attitude and Perception Of Participants Towards Vasectomysupporting
confidence: 90%
“…Sood et al also found that 52% of the men had fear of failure of vasectomy as it brings a bad name to wives in Punjab. 11 Fear of complications (3%) of the procedure after the surgery was another factor observed in our study which was coherent with studies done by Ayele et 8,12,13 These findings indicate the importance of addressing fears and providing adequate information to alleviate concerns and promote informed decision-making regarding the procedure.…”
Section: Attitude and Perception Of Participants Towards Vasectomysupporting
confidence: 90%
“…Vasectomy is a male method of contraceptive which is known and acceptable only in some developed countries of the world. Although it is safe and easy to perform, only 45 million couples worldwide rely on it [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A semi-structured questionnaire was used to collect the data by interviewing technique which was developed from relevant literature 5 , 6 , 8–11 , 13 , 14 and modified to the local context in such a way that all the variables to be assessed were included. The questionnaire consists of 4 sections with a total of 46 quantitative items.…”
Section: Methodsmentioning
confidence: 99%